Evaluation of the Impact of Static Interference on an Empirical Data Based Static Magnetic Localization Setup for Capsule Endoscopy - Zeising Samuel (De Gruyter, 2020)
In this paper, the impact of interference due to the geomagnetic field on a static magnetic localization setup for capsule endoscopy, which is suitable for a wearable application, was investigated. For this purpose, a study was carried out in which the average abdomen size of 15 subjects was evaluated. With the determined geometry values, a setup consisting of three elliptical sensor rings was modeled. Simulations were performed, where the magnetic flux density was evaluated at the sensors by using different-sized magnets. The measured values were compared with each other and the geomagnetic flux density. The results revealed that the measured values were for all evaluated magnet sizes of the order of the geomagnetic flux density, which is problematic since the calibration of sensors is no longer valid if the orientation of the wearable sensor array is changed. However, it is suggested that a differential measurement is suitable for the proposed system and could reduce static interference caused by the geomagnetic field.